State of the art of research of families with forced displacement in Colombia (Boletín Semillero de Investigación en Familia, 2021)
Introduction: Forced displacement due to violence has brought associated other problems, such as the violation of human rights that deeply affects individuals, families and society in general. Objective: to identify research in families that have suffered the phenomenon of forced displacement due to the armed conflict in the different regions of the country as a group or through one or more of its members. Materials and methods: the information search criteria were investigations or reviews carried out in Colombia on families or with any member of these who have suffered forced displacement due to armed violence, during the period 2012 - 2016. The search databases They were Scopus, Google Scholar, ScienceDirect, Lilacs, Redalyc and Clacso library. Results: the categories that emerged were characterization of the displaced population, health conditions and basic sanitation, consequences of the armed conflict and forced displacement, public policies and meanings of displacement, identity and citizenship. Conclusions: the traumatic experiences of forced displacement lead the human groups that suffer them to resignify the places where they live, the family itself, their places of origin and their links, as well as to generate transformations and consolidate community and social links to empower themselves and do assert the rights provided by public policy.
Keywords: armed conflict; family; internal migration; social policy.